Risk of Non-colorectal Malignancies in Sporadic Versus Lynch Syndrome-associated dMMR Colorectal Cancer - Gkekas, Ioannis; Novotny, Jan; Kaprio, Tuomas; Fabian, Pavel; Böckelman, Camilla; Edin, Sofia; Strigård, Karin; Svoboda, Tomas; Hagström, Jaana; Haglund, Caj; Palmqvist, Richard (Hellenic Anticancer Institute, 2026)
Background/Aim: Deficient mismatch repair (dMMR) colorectal cancer (CRC) arises from either sporadic epigenetic changes or hereditary Lynch syndrome. This retrospective multicenter cohort study is the first to evaluate the differences in risk for dMMR non-colorectal malignancy between patients with sporadic CRC and those with Lynch syndrome-associated CRC.
Patients and Methods: A cohort of 1,753 patients treated between 1996 and 2019 in Sweden, Finland, and the Czech Republic was evaluated for MMR status by immunohistochemistry and classified as either proficient (pMMR) or dMMR. The last one underwent BRAF V600E and MLH1 methylation testing to classify sporadic versus Lynch-associated cases. Non-CRC malignancies occurring within ±20 years of CRC diagnosis were identified via national cancer registries and medical records. Incidence rate ratios (IRRs) were estimated using Poisson regression adjusted for age, sex, tumor site, and stage.
Results: Among 277 dMMR cases (186 sporadic, 91 Lynch), 101 patients (36%) developed at least one non-CRC malignancy. Sporadic dMMR was associated with significantly lower risk compared to Lynch-associated dMMR [multivariable IRR=0.82; 95% confidence interval (CI)=0.51-0.91; p=0.014]. The reduced risk was consistent for malignancies occurring both before (IRR=0.48; p=0.047) and after CRC diagnosis (IRR=0.37; p=0.026). Age was an independent predictor of risk.
Conclusion: Sporadic dMMR CRC confers a substantially lower risk of non-colorectal malignancy than Lynch syndrome-associated CRC. These findings underscore the importance of incorporating MMR etiology into personalized surveillance strategies.